Modified lateral tarsal strip procedure in paralytic lower eyelid ectropion – a case report - Krajewska-Węglewicz, Larysa; Kurowska, Anna; Banach, Marta; Filipiak, Ewa; Sempińska-Szewczyk, Joanna; Skopiński, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
Paralytic lagophthalmos secondary to facial nerve palsy is a considerable functional and cosmetic issue. In advanced stages, it may lead to irreversible vision loss due to exposure keratopathy. However, there are various surgical methods available for the treatment of this condition. We present a case of an 81-year-old woman with a paralytic lower lid ectropion in the right eye, in whom a modified lateral tarsal strip procedure resulted in restoration of lid position, tension, and function, as well as a good aesthetic outcome. This method is widely used in the treatment of paralytic ectropion, both as a stand-alone procedure or in combination with other, more radical, methods. In case of treatment failure, the lateral tarsal strip procedure is not a contraindication to using other techniques. The procedure offers satisfactory aesthetic effects without visual field limitation, which remains crucial for many patients when deciding on the treatment modality.